Design and immunogenicity of a quadrivalent mRNA vaccine targeting HSV-2 with comparative evaluation of co-formulated and admixed formulations - Cho, Youngran; Lee, Chanwoo; Park, Sang-In; Kim, Yeongjun; Lee, Yu-Sun; Lee, Seonghyun; Yoon, Subin; Roh, Gahyun; Ha, Dahyeon; Oh, Ayoung; Cho, Kyusang; Lee, Jisun; et al. (Frontiers in Immunology, 2025)
IntroductionThe globally prevalent herpes simplex virus 2 (HSV-2) establishes lifelong latent infections in sensory neurons and causes recurrent genital disease. However, no vaccine is available to prevent HSV-2 infection. The mRNA vaccine platform offers distinct advantages over protein-based approaches, including rapid antigen design, scalable production, and efficient intracellular expression.MethodsA prophylactic quadrivalent mRNA vaccine encoding full-length HSV-2 glycoprotein B (gB2), C (gC2), D (gD2), and E (gE2) was developed. Its immunogenicity and protective efficacy were evaluated in a murine intravaginal challenge model.ResultsQuadrivalent mRNA vaccine-immunized mice showed robust HSV-2-specific immune responses, including high titers of neutralizing antibodies and strong T cell responses, which persisted for at least 16 weeks. Upon viral challenge, vaccinated animals were fully protected from genital disease and exhibited significantly reduced viral copy numbers in the genital tract. Vaccination also inhibited the establishment of latent infections in the dorsal root ganglia, as evidenced by markedly lower HSV-2 DNA levels than those in mock-vaccinated controls. Comparative analysis showed no significant difference between co-formulated and admixed lipid nanoparticle formulations, indicating flexibility in vaccine manufacturing without compromising efficacy.DiscussionThe quadrivalent mRNA vaccine provides strong and durable protection against both primary and latent infection, supporting its potential as a promising candidate for the prevention of genital herpes.